1995
DOI: 10.1002/hep.1840220619
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid influences cholesterol solubilization and microcrystal nucleation time in gallbladder bile

Abstract: Little is known about the effects of biliary deoxycholic acid on the partitioning of biliary cholesterol between vesicles and micelles and on the rate of nucleation of cholesterol microcrystals, key steps in gallstone formation. Therefore, 43 samples of fresh gallbladder bile were obtained from a heterogeneous group of patients with and without stones. Univariate and multivariate analyses were then applied to determine the inter-relationships between biliary cholesterol saturation, total lipid concentration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 48 publications
2
35
2
Order By: Relevance
“…Early studies by Low-Beer and Nutter (135) reported that treating control individuals with metronidazole, an antibiotic effective against anaerobic bacteria, significantly decreased the cholesterol saturation index of bile. Moreover, excess DCA in bile has been reported to decrease the nucleation time for cholesterol crystallization (136,137). In total, these results suggest a possible link between intestinal bacteria, DCA, and the risk of cholesterol gallstone disease in some patients.…”
Section: Secondary Bile Acids and Diseasementioning
confidence: 78%
“…Early studies by Low-Beer and Nutter (135) reported that treating control individuals with metronidazole, an antibiotic effective against anaerobic bacteria, significantly decreased the cholesterol saturation index of bile. Moreover, excess DCA in bile has been reported to decrease the nucleation time for cholesterol crystallization (136,137). In total, these results suggest a possible link between intestinal bacteria, DCA, and the risk of cholesterol gallstone disease in some patients.…”
Section: Secondary Bile Acids and Diseasementioning
confidence: 78%
“…Similarly, low serum levels of apo A have been linked to decreased cholesterol crystallization in the bile, 33 and low serum levels of HDL have been associated with increased biliary cholesterol saturation and bile acid hyposecretion, 8,[30][31][32] which reduces cholesterol solubility in the bile and leads to gallstone formation. 34 Although the exact role of low levels of total cholesterol and/or LDL in gallstone formation is unclear, a number of indirect observations suggest a possible inverse association between total cholesterol and gallstone pathogenesis. A higher prevalence of gallstones has been suggested among men on cholesterol-lowering diets and among subjects who experienced rapid weight loss, a behavior often correlated with lower cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Abcb11 transgenic mice display a characteristic lithogenic phenotype including rapidly recycling of bile salts, a more hydrophobic bile salt pool, and enrichment with TDC, the secondary bile salt metabolized from cholate by the colonic flora (41,42). Cholesterol gallstone patients have been reported to display higher biliary TDC concentrations compared with stone-free controls (43), and increased TDC levels promote cholesterol crystallization in model and human biles in vitro (13,44). Also of note, a recent genome-wide analysis in inbred mice identified higher hepatic gene expression of both FXR and SHP in mice carrying gallstone susceptibility alleles at these loci (45), as was observed in our transgenic mice.…”
Section: Abcb11 Overexpression Alters Hepatic Lipid Metabolismmentioning
confidence: 99%